2011
DOI: 10.1007/s11468-011-9297-1
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Transmission of Three-Dimensional Crescent-like Holes Arrays

Abstract: We developed a method to fabricate a periodic array of three-dimensional crescent-like holes (3DCLH) via an inverted hemispherical colloidal lithography. It is found that there exists an extraordinary optical transmission in this non-planar perforated periodic array of 3DCLH when the electric field of the incident light is perpendicular to the cross-line of the crescent-like hole. This extraordinary optical peak is insensitive with the incident angles and sensitive with the angle between the electric field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…They achieved around 30% transmittance through MNSA. The response of periodic subwavelength plasmonic structures for incoming radiation in reflection or transmission mode depends on geometrical parameters of the structure such as period, size, shape, and surface roughness [ 62 65 ]. It was both experimentally and theoretically demonstrated that by tuning the geometrical parameters of periodic grating structure, it is possible to excite various types of cavity modes or even higher order of plasmonic modes with varying sensor sensitivity [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…They achieved around 30% transmittance through MNSA. The response of periodic subwavelength plasmonic structures for incoming radiation in reflection or transmission mode depends on geometrical parameters of the structure such as period, size, shape, and surface roughness [ 62 65 ]. It was both experimentally and theoretically demonstrated that by tuning the geometrical parameters of periodic grating structure, it is possible to excite various types of cavity modes or even higher order of plasmonic modes with varying sensor sensitivity [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…They achieved around 30% transmittance through MNSA. The response of periodic subwavelength plasmonic structures for incoming radiation in reflection or transmission mode depends on geometrical parameters of the structure such as period, size, shape, and surface roughness [62][63][64][65]. It was both experimentally and theoretically demonstrated that by tuning the geometrical parameter of periodic grating structure, it is possible to excite various types of cavity modes or even higher order of plasmonic modes with varying sensor sensitivity [66].…”
Section: Introductionmentioning
confidence: 99%
“…This effect leads to field amplification both inside and outside (in the near-field zone) the metal nanoparticles. These resonances, which may be used in optical sensing, generally depend on the type of metal, the shape of nanoparticles and the dielectric environment within the electromagnetic near field [2][3][4][5][6][7]. Nanoparticles are also used to constitute a subwavelength waveguide.…”
Section: Introductionmentioning
confidence: 99%